2018
DOI: 10.1051/matecconf/201824503005
|View full text |Cite
|
Sign up to set email alerts
|

Increase of fire resistance of reinforced concrete structures with polypropylene microfiber

Abstract: The increase in the construction of high-rise, technically complex buildings and structures is a prerequisite for the widespread use of structures of heavy concrete. In this work, a special type of destruction of this type of concrete is considered in the fire action explosive spalling. One method of protection is polypropylene microfiber, the objective of which is to increase the fire resistance of concrete and reinforced concrete structures. The fire resistance tests of the reinforced concrete structure with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Li et al [21] noted that heated metallic microfibers tended to lose adhesiveness with the UHPC matrix and cause damage to the structural element. However, Gravit and Golub [22] reported that even though metallic fibers had higher melting points than polymer fibers, they could still contribute to spalling mitigation in hybrid compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [21] noted that heated metallic microfibers tended to lose adhesiveness with the UHPC matrix and cause damage to the structural element. However, Gravit and Golub [22] reported that even though metallic fibers had higher melting points than polymer fibers, they could still contribute to spalling mitigation in hybrid compounds.…”
Section: Introductionmentioning
confidence: 99%